AMPK-Dependent Mechanisms but Not Hypothalamic Lipid Signaling Mediates GH-Secretory Responses to GHRH and Ghrelin - María J. Vázquez (Cells, 2020)
GH (growth hormone) secretion/action is modulated by alterations in energy homeostasis, such as malnutrition and obesity. Recent data have uncovered the mechanism by which hypothalamic neurons sense nutrient bioavailability, with a relevant contribution of AMPK (AMP-activated protein kinase) and mTOR (mammalian Target of Rapamycin), as sensors of cellular energy status. However, whether central AMPK-mediated lipid signaling and mTOR participate in the regulation of pituitary GH secretion remains unexplored. We provide herein evidence for the involvement of hypothalamic AMPK signaling, but not hypothalamic lipid metabolism or CPT-1 (carnitine palmitoyltransferase I) activity, in the regulation of GH stimulatory responses to the two major elicitors of GH release in vivo, namely GHRH (growth hormone–releasing hormone) and ghrelin. This effect appeared to be GH-specific, as blocking of hypothalamic AMPK failed to influence GnRH (gonadotropin-releasing hormone)-induced LH (luteinizing hormone) secretion. Additionally, central mTOR inactivation did not alter GH responses to GHRH or ghrelin, nor this blockade affected LH responses to GnRH in vivo. In sum, we document here for the first time the indispensable and specific role of preserved central AMPK, but not mTOR, signaling, through a non-canonical lipid signaling pathway, for proper GH responses to GHRH and ghrelin in vivo.